Cerebral haemodynamic response to somatosensory stimulation in preterm lambs is enhanced following sildenafil and inhaled nitric oxide administration - Inocencio, Ishmael Miguel; Kaur, Navneet; Tran, Nhi T.; Wong, Flora Y. (Frontiers in Physiology, 2023)
Background: Neurovascular coupling (NVC) leads to an increase in local cerebral blood flow and oxygenation in response to increased neural activity and metabolic demand. Impaired or immature NVC reported in the preterm brain, potentially reduces cerebral oxygenation following increased neural activity, predisposing to cerebral tissue hypoxia. Endogenous nitric oxide (NO) is a potent vasodilator and a major mediator of NVC and the cerebral haemodynamic response. NO modulators, such as inhaled nitric oxide (iNO) and sildenafil, induce vasodilation and are used clinically to treat pulmonary hypertension in preterm neonates. However, their impact on NVC in the preterm brain are unknown. We aimed to characterise the cerebral functional haemodynamic response in the preterm brain exposed to NO modulators. We hypothesized that iNO and sildenafil in clinical dosages would increase the baseline cerebral perfusion and the cerebral haemodynamic response to neural activation. Methods: Preterm lambs (126–7 days’ gestation) were delivered and mechanically ventilated. The cerebral functional haemodynamic response was measured using near infrared spectroscopy as changes in cerebral oxy- and deoxyhaemoglobin (ΔoxyHb, ΔdeoxyHb), following left median nerve stimulations of 1.8, 4.8, and 7.8 s durations in control preterm lambs (n = 11), and following 4.8 and 7.8 s stimulations in preterm lambs receiving either sildenafil citrate (n = 6, 1.33 mcg/kg/hr) or iNO (n = 8, 20 ppm). Results: Following 1.8, 4.8, and 7.8 s stimulations, ∆oxyHb in the contralateral cortex increased (positive functional response) in 7/11 (64%), 7/11 (64%), and 4/11 (36%) control lambs respectively (p < 0.05). Remaining lambs showed decreased ΔoxyHb (negative functional response). Following 4.8 s stimulations, more lambs receiving sildenafil or iNO (83% and 100% respectively) showed positive functional response compared to the controls (p < 0.05). No significant difference between the three groups was observed at 7.8 s stimulations. Conclusion: In the preterm brain, prolonged somatosensory stimulations increased the incidence of negative functional responses with decreased cerebral oxygenation, suggesting that cerebral oxygen delivery may not match the oxygen demand. Sildenafil and iNO increased the incidence of positive functional responses, potentially enhancing NVC, and cerebral oxygenation.